Perception of Sexual Education: Barriers and Implications in Guidance and Counseling Services - Saripah, Ipah (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2021)
Sexual behavior in adolescence becomes prone and risky when not accompanied by an understanding of healthy sexual behavior. Many teenagers do not understand sexual education so do various forms of deviation. And overall, adolescents have had a good perception of sexual education, shown with an average score of 37,964 and an attainment rate of 74.4% that is in the healthy category, and the implications of guidance and counseling services on sexual education in schools have already begun to take effect, but are still not compressive overall. This research aims to find out perceptions of sexual education and barriers and implications in guidance and counseling services in schools. The method used in this study uses a qualitative and qualitative approach, with a sample of 618 respondents from private high schools, public high schools, and vocational schools, and the implementation of focus group discussion whose participants are teachers from high school and vocational school.